1967
DOI: 10.1139/p67-340
|View full text |Cite
|
Sign up to set email alerts
|

Ion Implantation of Silicon: Ii. Electrical Evaluation Using Hall-Effect Measurements

Abstract: Hall-effect and sheet-resistivity measurements have been made on silicon samples implanted with Sb, Ga, and As ions at energies between 20 and 75 keV. These measurements determine the weighted average of the number Ns of carriers/cm2 and the carrier mobility in the implanted layer. A combination of Hall measurements and layer-removal techniques was used in some cases to obtain a more accurate value of the number of carriers/cm2 and the depth dependence of the carrier concentration and mobility.For Sb implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

1971
1971
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…For H4, the effective concentration value N s is 3.13 x 10 18 cm −3 whereas N d is 4.18 x 10 18 cm −3 . N s is therefore about 75 % of N d , a figure similar to that found by Mayer [18] in implanted layers of silicon. For all of the p-type layers which were sectioned and probed at successive depths, the transition from p-to n-type material was found to correspond fairly closely (∼ 3 µm) to the position of the p-n junction as shown in the staining procedure.…”
Section: Resultssupporting
confidence: 86%
“…For H4, the effective concentration value N s is 3.13 x 10 18 cm −3 whereas N d is 4.18 x 10 18 cm −3 . N s is therefore about 75 % of N d , a figure similar to that found by Mayer [18] in implanted layers of silicon. For all of the p-type layers which were sectioned and probed at successive depths, the transition from p-to n-type material was found to correspond fairly closely (∼ 3 µm) to the position of the p-n junction as shown in the staining procedure.…”
Section: Resultssupporting
confidence: 86%
“…1(b), which is approximately 33% in volume fraction for the supersaturated solid solution of Ag in Si. The dosage-threshold for amorphization of Si by Ag-ions, expected to be close to that of Sb, is estimated to be on order of 10 14 Ag-atoms/cm 2 as reported in the literature [8,9].…”
Section: Characterization Of the Npsmentioning
confidence: 60%
“…It contains most of the Ag NPs thus formed. The sharp boundary between the amorphized region and the underlying defect-laden region, though largely still crystalline, manifests that the dosage threshold of irradiation-induced amorphization [8,9] has been reached or surpassed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depth profiles of carrier concentration and carrier mobility were accomplished by using these measurements in conjunction with anodic oxidation and HF layer removal techniques as outlined [4] by Mayer et al The details of the experimental procedure have been reported [5]. Annealing was conducted in a nitrogen atmosphere.…”
Section: • Electrical Evaluation Of Implanted Layersmentioning
confidence: 99%